The provisional OMERACT ultrasonography score for giant cell arteritis - İNANÇ, GÜZİDE NEVSUN (My University, 2023)
Objectives To develop an Outcome Measures in Rheumatology (OMERACT) ultrasonography score for monitoring disease activity in giant cell arteritis (GCA) and evaluate its metric properties. Methods The OMERACT Instrument Selection Algorithm was followed. Forty-nine members of the OMERACT ultrasonography large vessel vasculitis working group were invited to seven Delphi rounds. An online reliability exercise was conducted using images of bilateral common temporal arteries, parietal and frontal branches as well as axillary arteries from 16 patients with GCA and 7 controls. Sensitivity to change and convergent construct validity were tested using data from a prospective cohort of patients with new GCA in which ultrasound-based intima-media thickness (IMT) measurements were conducted at weeks 1, 3, 6, 12 and 24. Results Agreement was obtained (92.7%) for the OMERACT GCA Ultrasonography Score (OGUS), calculated as follows: sum of IMT measured in every segment divided by the rounded cut-off values of IMTs in each segment. The resulting value is then divided by the number of segments available. Thirty-five members conducted the reliability exercise, the interrater intraclass correlation coefficient (ICC) for the OGUS was 0.72-0.84 and the median intrareader ICC was 0.91. The prospective cohort consisted of 52 patients. Sensitivity to change between baseline and each follow-up visit up to week 24 yielded standardised mean differences from -1.19 to -2.16, corresponding to large and very large magnitudes of change, respectively. OGUS correlated moderately with erythrocyte sedimentation rate, C reactive protein and Birmingham Vasculitis Activity Score (corr coeff 0.37-0.48). Conclusion We developed a provisional OGUS for potential use in clinical trials.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; ROMATOLOJİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; MOLECULAR BIOLOGY & GENETICS; ALLERGY; RHEUMATOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Romatoloji; İmmünoloji ve Alerji; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Rheumatology; Immunology and Allergy; Immunology; General Biochemistry, Genetics and Molecular Biology; giant cell arteritis; ultrasonography; outcome assessment; health care; systemic vasculitis; ULTRASOUND; TOCILIZUMAB; SONOGRAPHY; TRIAL; outcome assessment, health care